Coumarin-based fluorescent compound, fluorescent sensitive film and preparation method and application of coumarin-based fluorescent compound

By combining fragrance -based fluorescent compounds with chitosan base membrane to prepare a fluorescent sensitive film with a honeycomb structure, it solves the problem of detection and removal of lead ions in water in the existing technology. Efficient removal, and low material cost and environmental protection.

CN119350312AActive Publication Date: 2025-01-24LANZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411467873.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The prior art is difficult to achieve rapid, sensitive and efficient detection and removal of lead ions in water, and the traditional methods are cumbersome to operate and complex instruments, which have problems such as secondary contamination and sample pretreatment.

Method used

The combination of fragrance -based fluorescent compounds and chitosan base membranes is used to prepare a fluorescent sensitive film with a honeycomb structure through the combination of the coordination and electrostatic adsorption, which increases the contact area between metal ions and the membrane. Sensitive detection and efficient adsorption.

Benefits of technology

It achieves ultra-sensitive detection and efficient removal of lead ions in water, with a detection limit as low as 5 ppb, low material cost, easy integration, and no secondary pollution to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350312A_ABST
    Figure CN119350312A_ABST
Patent Text Reader

Abstract

The invention relates to a coumarin-based fluorescent compound, a fluorescent sensitive film as well as a preparation method and application of the coumarin-based fluorescent compound. The coumarin-based fluorescent compound provided by the invention has a structure as shown in a formula I. The fluorescent sensitive film provided by the invention comprises a chitosan-based film and the coumarin-based fluorescent compound. The fluorescent sensitive membrane provided by the invention has an enrichment effect on heavy metal ions, especially Pb < 2 + >, in water, sample preparation is not needed during detection and adsorption, and the detection and adsorption efficiency can be effectively improved. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of thin film sensitive materials and heavy metal detection and removal technology, and in particular, relates to a coumarin-based fluorescent compound and a fluorescent sensitive membrane for detecting and removing lead ions in water. The present application also relates to a method for preparing the fluorescent sensitive membrane. Background Art

[0002] Lead ion (Pb 2+ ) pollution is one of the main problems of groundwater pollution. Non-degradable Pb in water 2+ It not only harms the ecosystem, but also accumulates in water and enters the human body, posing a serious threat to human health. Its accumulation can cause nerve damage, kidney damage, and muscle paralysis. Therefore, it is urgent to develop a suitable technology to detect Pb in groundwater. 2+ Provides sensitive on-site monitoring and efficient removal to protect human health.

[0003] Traditional Pb 2+ Detection methods include atomic absorption spectroscopy (AAS), inductively coupled plasma atomic emission spectroscopy (ICP-AES) and capillary electrophoresis (CE). These methods have the advantages of good specificity and mature instruments, but the cumbersome operation, complex instruments, and difficult pretreatment processes limit their rapid and sensitive detection. Fluorescence has become a very powerful technology that can quickly and sensitively detect analytes through changes in fluorescence signals. At the same time, fluorescent sensors have the advantages of low cost, small size, easy integration, and real-time monitoring. They are currently the most widely used and researched sensors. Among them, organic small molecule fluorescent sensors are mostly powdery, which may cause secondary pollution to water bodies, and the post-processing is complicated. Most of them only have the ability to detect Pb 2+ There are still huge challenges in practical applications. Summary of the invention

[0004] In order to solve the problems in the prior art, the present application provides a coumarin-based fluorescent compound and a fluorescent sensitive membrane and a preparation method and application thereof. The fluorescent sensitive membrane of the present application can be used for ultra-sensitive detection and efficient removal of metal ions, especially lead ions, in actual water samples.

[0005] In a first aspect, the present application provides a coumarin-based fluorescent compound, the structure of which is shown in Formula I:

[0006]

[0007] In formula I, X is selected from O or S, L is absent or selected from C1-C6 alkylene;

[0008] R1 and R2 are the same or different and are independently selected from C1-C6 alkyl groups;

[0009] R3, R4, R5, R6, R7, R8 and R9 are each independently selected from hydrogen, halogen or C1-C6 alkyl.

[0010] In some embodiments, X is selected from O, and L is absent or selected from C1-C4 alkylene, such as methylene, ethylene, propylene, isopropylene, butylene, isobutylene, or tert-butylene.

[0011] In some embodiments, R1 and R2 are the same or different and are independently selected from C1-C4 alkyl groups, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl or tert-butyl.

[0012] In some embodiments, R3, R4, R5, R6, R7, R8 and R9 are each independently selected from hydrogen, fluorine, chlorine, bromine or C1-C4 alkyl.

[0013] In some embodiments, R3, R4, R5 and R6 are the same and are selected from hydrogen, fluorine, chlorine, bromine or C1-C4 alkyl, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl or tert-butyl.

[0014] In some embodiments, R7, R8 and R9 are the same and are selected from hydrogen, fluorine, chlorine, bromine or C1-C4 alkyl, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl or tert-butyl.

[0015] In some embodiments, the coumarin-based fluorescent compound is selected from the following compounds:

[0016]

[0017] In a second aspect, the present application provides a fluorescence sensitive membrane, which includes a chitosan-based membrane and the coumarin-based fluorescent compound described in the first aspect.

[0018] The present invention uses the coordination and electrostatic adsorption between the flexible chitosan-based membrane and the fluorophore (coumarin-based fluorescent compound) to prepare a fluorescent sensitive membrane. The sensitive membrane has a large number of interconnected pore structures, which not only provides a convenient and rapid mass transfer channel inside and outside the membrane, but also increases the membrane and metal ions, especially Pb 2+ The contact area between the two surfaces is important for achieving sensitive on-site detection and efficient adsorption of heavy metal ions, especially Pb 2+ key factors.

[0019] In some embodiments, the chitosan-based film is combined with the coumarin-based fluorescent compound via chemical bonds and / or intermolecular forces.

[0020] In some embodiments, the loading amount of the coumarin-based fluorescent compound on the chitosan-based membrane is 1 mg / g-30 mg / g, for example, 1.5 mg / g, 2 mg / g, 2.5 mg / g, 3 mg / g, 3.5 mg / g, 4 mg / g, 4.5 mg / g, 5 mg / g, 5.5 mg / g, 6 mg / g, 6.5 mg / g, 7 mg / g, 7.5 mg / g, 8 mg / g, 8.5 mg / g, 9 mg / g, 9.5 mg / g, 10 mg / g, 11 mg / g, 12 mg / g, 13 mg / g, 14 mg / g, 15 mg / g, 16 mg / g, 17 mg / g, 18 mg / g, 19 mg / g, 20 mg / g, 22 mg / g, 24 mg / g, 26 mg / g or 28 mg / g. In some embodiments, the loading amount of the coumarin-based fluorescent compound on the chitosan-based membrane is 2.5 mg / g-4.3 mg / g. In some embodiments, the loading amount of the coumarin-based fluorescent compound on the chitosan-based membrane is 2.5 mg / g-4.3 mg / g.

[0021] In some embodiments, the loading amount of the coumarin-based fluorescent compound on the chitosan-based membrane is greater than 1 mg / g, for example, 50 mg / g, 150 mg / g, 200 mg / g, 250 mg / g or 300 mg / g.

[0022] In some embodiments, the thickness of the fluorescence sensitive film is 10 μm-50 μm, such as 13 μm, 15 μm, 17 μm, 20 μm, 23 μm, 25 μm, 27 μm, 30 μm, 33 μm, 35 μm, 37 μm, 40 μm, 43 μm, 45 μm or 47 μm. In some embodiments, the thickness of the fluorescence sensitive film is 15 μm-35 μm. In some embodiments, the thickness of the fluorescence sensitive film is 16.70 μm-32.54 μm.

[0023] In a third aspect, the present application provides a method for preparing a fluorescence sensitive film, which comprises the following steps:

[0024] S1: subjecting the compounds represented by formula A and formula B to a first reaction in a solvent to obtain a reaction product;

[0025] S2: performing a second reaction on the reaction product of step S1 and a solution containing a chitosan-based membrane;

[0026]

[0027] In formula A, R1 and R2 are the same or different and are independently selected from C1-C6 alkyl; R3, R4, R5 and R6 are independently selected from hydrogen, halogen or C1-C6 alkyl;

[0028] In formula B, X is selected from O or S, L is absent or selected from C1-C6 alkylene; R7, R8 and R9 are each independently selected from hydrogen, halogen or C1-C6 alkyl.

[0029] In some embodiments, in Formula A, R1 and R2 are the same or different, and are independently selected from C1-C4 alkyl groups, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl or tert-butyl.

[0030] In some embodiments, in Formula A, R3, R4, R5 and R6 are each independently selected from hydrogen, fluorine, chlorine, bromine or C1-C4 alkyl, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl or tert-butyl.

[0031] In some embodiments, in formula B, X is selected from O, and L is absent or selected from C1-C4 alkylene, such as methylene, ethylene, propylene, isopropylene, butylene, isobutylene or tert-butylene.

[0032] In some embodiments, in Formula B, R7, R8 and R9 are each independently selected from hydrogen, fluorine, chlorine, bromine or C1-C4 alkyl, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl or tert-butyl.

[0033] In some embodiments, the compound represented by formula A is selected from the following compounds:

[0034] (7-(Diethylamino)coumarin-3-carboxaldehyde),

[0035]

[0036] In some embodiments, the compound represented by formula B is selected from the following compounds:

[0037] (2-furoylhydrazide),

[0038] In some embodiments, in step S1, the solvent is selected from C1-C5 alcohol compounds. In some embodiments, the solvent is selected from methanol or ethanol.

[0039] In some embodiments, in step S1, the molar ratio of the compound represented by formula A to the compound represented by formula B is (0.8-1.2):1, for example, 0.85:1, 0.9:1, 0.95:1, 1:1, 1.05:1, 1.1:1 or 1.15:1.

[0040] In some embodiments, in step S1, the temperature of the first reaction is 50° C.-100° C., for example, 60° C., 65° C., 70° C., 75° C., 80° C. or 85° C. In some embodiments, the temperature of the first reaction is 60° C.-90° C.

[0041] In some embodiments, the first reaction time is 5h-30h, for example, 7h, 10h, 13h, 15h, 17h, 20h, 23h, 25h or 27h. In some embodiments, the first reaction time is 10h-20h.

[0042] In some embodiments, the reaction product is recrystallized and then subjected to a second reaction with a solution containing a chitosan-based membrane. In some embodiments, a C1-C5 alcohol compound is used, preferably methanol or ethanol, for recrystallization.

[0043] In some embodiments, in step S2, the mass ratio of the reaction product to chitosan is 0.001-0.5, for example, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.011, 0.012, 0.013, 0.014, 0.015, 0.016, 0.017, 0.018, 0.019, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4 or 0.45. In some embodiments, the mass ratio of the reaction product to chitosan is 0.005-0.1. In some embodiments, the mass ratio of the reaction product to chitosan is 0.005-0.015.

[0044] In some embodiments, in step S2, the temperature of the second reaction is 5° C.-35° C., for example, 10° C., 15° C., 20° C., 25° C. or 30° C. In some embodiments, the temperature of the second reaction is 10° C.-30° C. In some embodiments, the temperature of the second reaction is room temperature.

[0045] In some embodiments, in step S2, the second reaction time is 5h-30h, for example, 7h, 10h, 13h, 15h, 17h, 20h, 23h, 25h or 27h. In some embodiments, the second reaction time is 10h-20h.

[0046] In some embodiments, in step S2, the solution containing the chitosan-based membrane is obtained by:

[0047] The chitosan is dissolved in an acid solution to obtain an acid solution of chitosan; the acid solution of chitosan is mixed with a polyol and then subjected to a prepolymerization reaction to obtain the solution containing the chitosan-based membrane.

[0048] In some embodiments, the acid solution is selected from one or more of acetic acid, lactic acid, and propionic acid.

[0049] In some embodiments, the acid solution has an acid content of 0.5-5%, such as 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or 4.5%. In some embodiments, the acid content is 0.5-2%.

[0050] In some embodiments, the polyol is selected from one or more of C2-C6 polyols. In some embodiments, the polyol is selected from ethylene glycol or glycerol.

[0051] In some embodiments, the ratio of the mass of the chitosan to the total volume of the acid solution and the polyol is (1-4) g:100 mL, for example, 1.3 g:100 mL, 1.5 g:100 mL, 1.7 g:100 mL, 2.0 g:100 mL, 2.3 g:100 mL, 2.5 g:100 mL, 2.7 g:100 mL, 3.0 g:100 mL, 3.3 g:100 mL, 3.5 g:100 mL or 3.7 g:100 mL. In some embodiments, the ratio of the mass of the chitosan to the total volume of the acid solution and the polyol is (2-3) g:100 mL.

[0052] In some embodiments, the volume ratio of the acid solution to the polyol is (95-99):(1-5), for example, 98:2, 97:3 or 96:4.

[0053] In some embodiments, the preparation method further comprises step S3: evaporating and cooling the reaction product of step S2 to obtain a crude film, and washing the crude film to obtain the fluorescent sensitive film.

[0054] In some embodiments, the evaporation temperature is 40°C-65°C, for example, 45°C, 50°C, 55°C or 60°C.

[0055] In some embodiments, the washing comprises washing the crude membrane with water until it is neutral.

[0056] In some embodiments, the preparation of the fluorescence sensitive membrane comprises the following steps:

[0057] (1) A fluorophore was prepared using 7-(diethylamino)coumarin-3-carboxaldehyde, 2-furoylcarboxylic acid hydrazide and ethanol;

[0058] (2) stirring chitosan and acetic acid until chitosan is completely dissolved; then adding glycerol and prepolymerizing at room temperature to obtain a chitosan base film solution;

[0059] (3) adding the above-mentioned fluorophore to the chitosan-based membrane solution for reaction;

[0060] (4) The solution after the reaction is evaporated and cooled to obtain a crude membrane, and the crude membrane is washed with water, preferably until it is neutral, to obtain the fluorescent sensitive membrane.

[0061] In some embodiments, the method for preparing the fluorescence sensitive film comprises the following specific steps:

[0062] 1) Preparation of fluorophore CM-L:

[0063] 7-(Diethylamino)coumarin-3-carboxaldehyde (preferably 245 mg, 1 mmol) and 2-furoylcarboxylic acid hydrazide (preferably 126 mg, 1 mmol) are dissolved in ethanol (preferably 20 mL), and the mixed solution is stirred at a temperature of, for example, 85° C. for, for example, 12 h, and then subjected to rotary distillation to obtain a brown crude product, which is recrystallized from ethanol to obtain the fluorophore CM-L.

[0064] 2) Preparation of ultra-sensitive membrane for detecting lead ions in water:

[0065] Chitosan (preferably 1.75 g) and 1% acetic acid (preferably 97 mL) are added to a single-necked flask and stirred until the chitosan is completely dissolved. Then, glycerol (preferably 3 mL) is added to prepolymerize at room temperature, for example, for 4 hours, to obtain a chitosan-based film solution. Finally, the fluorophore CM-L (e.g., 17 mg) is added and the reaction is continued, for example, for 12 hours. The solution is poured into a glass dish and evaporated and cooled to obtain a crude film. The crude film is rinsed with water until neutral (three times) to obtain a CM-L / CG film.

[0066] In a third aspect, the present application provides the use of the coumarin-based fluorescent compound described in the first aspect, the fluorescent sensitive membrane described in the second aspect, or the fluorescent sensitive membrane prepared by the preparation method described in the third aspect in detecting and / or removing heavy metal ions, especially lead ions, in water.

[0067] Compared with the prior art, the beneficial effects of this application are:

[0068] 1) A new type of CM-L / CG thin film quenching fluorescent probe was prepared by using the coordination and electrostatic adsorption between the flexible chitosan-based membrane and the fluorophore.

[0069] 2) CM-L / CG film has strong adsorption capacity, good hydrophilicity and water stability, and can enrich lead ions in water. No sample preparation is required during detection and adsorption, which can improve detection efficiency.

[0070] 3) The materials used to prepare the CM-L / CG film are low-cost, will not cause secondary pollution to the environment and are easy to integrate, and can be applied to the detection and removal of actual groundwater samples. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Figure 1 is a scanning electron microscope (SEM) image of the CG base film in Example 1 of the present invention.

[0072] Figure 2 is a scanning electron microscope (SEM) image of the CM-L / CG film in Example 1.

[0073] Figure 3 is the linear titration graph of the CM-L / CG film in Example 1.

[0074] Figure 4 This is a graph showing the selectivity and anti-interference properties of the CM-L / CG film for cations in Example 1.

[0075] Figure 5 This is a graph showing the selectivity and anti-interference properties of the CM-L / CG film for anions in Example 1.

[0076] Figure 6 This is the kinetic adsorption curve of the CM-L / CG film in Example 2.

[0077] Figure 7 It is the isothermal adsorption curve of the CM-L / CG film in Example 2. DETAILED DESCRIPTION

[0078] In order to make the purpose, technical scheme and advantages of the present application clearer, the present application is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present application and are not intended to constitute any limitation to the present application. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.

[0079] The present application is further described below through specific examples.

[0080] Example 1

[0081] (1) 7-(Diethylamino)coumarin-3-carboxaldehyde (245 mg, 1 mmol) and 2-furoylcarboxylic acid hydrazide (126 mg, 1 mmol) were dissolved in ethanol (20 mL) to obtain a mixed solution. The mixed solution was stirred at 85°C for 12 h and then subjected to rotary distillation to obtain a brown crude product. The crude product was recrystallized from ethanol to obtain the fluorophore CM-L Yield: 291 mg; Yield: 82%.

[0082] 1 H NMR(400MHz,DMSO-d6)δ:11.91(s,1H),8.48(s,1H),8.33(s,1H),7.93(s,1H),7.64(d,J=9.0Hz,1H),7.30(s,1H ), 6.75 (dd, J = 9.1, 2.4Hz, 1H), 6.69 (s, 1H), 6.56 (d, J = 2.6Hz, 1H), 3.45 (q, J = 7.0Hz, 4H), 1.13 (d, J = 6.9Hz, 6H).

[0083] 13 C NMR(101MHz,DMSO-d6)δ:161.29,156.57,153.95,151.35,146.60,145.89,142.3 9,138.69,130.92,114.83,112.51,112.10,109.74,108.09,96.39,44.26,12.38.

[0084] ESI-MS (m / z): Calculated value: 353.1376. Found value: 353.3166.

[0085] (2) Chitosan (1.75 g) and 1% acetic acid (97 mL) were added to a single-necked flask and stirred until the chitosan was completely dissolved. Then, propylene glycol (3 mL) was added and prepolymerized at room temperature for 4 h to obtain a chitosan-based membrane solution. Finally, the fluorophore CM-L (17 mg) was added and the reaction was continued for 12 hours. The reaction solution was poured into a glass dish and evaporated and cooled to obtain a crude film. After the crude film was rinsed with water three times, a fluorescent sensitive film (CM-L / CG film) was obtained.

[0086] Figure 1 is a scanning electron microscope image of a CG film. The CG film is obtained by freeze-drying the chitosan base film solution obtained in step (2).

[0087] Figure 2 The scanning electron microscope image of the synthesized CM-L / CG film is shown in Figure 2. Figure 2 As shown, the CM-L / CG film has a honeycomb structure, the fluorescent group CM-L and CG are entangled and cross-linked with each other, and the prepared CM-L / CG film is denser and more uniform than the independent CG film.

[0088] Example 2

[0089] (1) The preparation of the fluorophore CM-L is the same as in Example 1.

[0090] (2) Chitosan (1.75 g) and 1% acetic acid (97 mL) were added to a single-necked flask and stirred until the chitosan was completely dissolved. Then, propylene glycol (3 mL) was added and prepolymerized at room temperature for 4 h to obtain a chitosan-based membrane solution. Finally, the fluorophore CM-L (500 mg) was added and the reaction was continued for 12 hours. The reaction solution was poured into a glass dish and evaporated and cooled to obtain a crude film. After the crude film was rinsed with water three times, a fluorescent sensitive film (CM-L / CG film) was obtained.

[0091] Application Examples

[0092] Application Example 1-Detection of Solid Fluorescence of CM-L / CG Thin Film

[0093] Cut the CM-L / CG film prepared in Example 1 into 6mm×6mm square film sheets, fix one of the film sheets on a glass slide, and dry the water with filter paper. Take 50mL of secondary water in a beaker, put the glass slide with the film sheet in it, soak it for 2-5min, then take it out, dry the water on the surface of the film sheet with filter paper, and then drip 10μL of secondary water on the film sheet to ensure that the water content of the film sheet is consistent. Press the film sheet on the glass slide with a quartz sheet, and detect the initial fluorescence intensity of the film sheet on a fluorescence spectrophotometer.

[0094] Then, the quartz plate was removed, and the glass slide with the film fixed was placed in 20 mL of the test solution. Then, 1 μL of Pb-containing 2+ ion solution (concentration of 100ppm), mixed evenly, and obtained a mixed solution with a concentration of 5ppb to be tested. The glass slide with the film fixed on it was soaked in the mixed solution for 2-5min and then taken out. The water on the surface of the film was first absorbed with filter paper, and then 10μL of secondary water was dripped on the film to ensure that the water content of the film was consistent. Then another quartz sheet was used to press the film tightly, and the fluorescence intensity change of the film was detected on a fluorescence spectrophotometer.

[0095] The detection method of the test solution with other concentrations (10ppb, 15ppb, 20ppb, 25ppb, 30ppb, 35ppb, 40ppb) is the same as that of the test solution with a concentration of 5ppb. Figure 3 The corresponding concentration-fluorescence intensity standard working curve is shown.

[0096] from Figure 3 As can be seen from the standard curve, as the Pb 2+ As the ion concentration increases, the fluorescence intensity of the sensitive membrane gradually decreases. 2+ When the ion concentration is 5ppb, it contains Pb 2+ The fluorescence intensity of the ion-sensitive membrane is significantly lower than that of the blank membrane, that is, when using fluorescence emission spectroscopy to detect Pb 2+When the detection limit of the sensitive membrane prepared by the present invention is lower than 5 ppb, the actual detection limit can be as low as 5 ppb.

[0097] Application Example 2-Specific Recognition of Lead Ions by CM-L / CG Film (Selectivity and Anti-interference)

[0098] First prepare the following solutions:

[0099] 1) 20mL of 400ppb Pb 2+ Solution;

[0100] 2) 20 mL of other metal ion solutions with a concentration of 4 ppm (equivalent: 10 times). Other metal ion solutions include KCl solution, MgCl2 solution, AlCl3 solution, CrCl3·3H2O solution, ZnCl2 solution, FeCl3 solution, CuCl2·2H2O solution, CdCl2·2.5H2O, HgCl2 solution, NaI solution, Na2SO4 solution, Na2S2O3 solution, Na2S·9H2O solution, NaNO3 solution, NaSCN solution, NaNO2 solution, CH3COONa solution and NaBr solution.

[0101] The CM-L / CG film prepared in Example 1 was then cut into 6mm×6mm square films and fixed on a glass slide. The water on the film was absorbed with filter paper, and 10μL of secondary water was dripped into it to ensure that the water content of the film was consistent. The glass slide containing the film was then immersed in 20mL of the above-mentioned test solution. The initial fluorescence intensity of each 6mm×6mm square film was first tested, and then the fluorescence intensity in the presence of different ions was tested. Finally, the Pb 2+ Fluorescence intensity in the presence of other ions.

[0102] Figure 4 This is a graph showing the selectivity and anti-interference properties of the sensitive membrane prepared in Example 1 to cations. Figure 5 The figure shows the selectivity and anti-interference performance of the sensitive membrane prepared in Example 1 to anions. Figure 4 and Figure 5 It can be seen that by comparing the changes in fluorescence intensity, it is found that only the lead ion solution causes a significant change in the fluorescence intensity of the film, indicating that the sensitive membrane of the present invention has excellent selectivity and anti-interference properties for lead ions.

[0103] Application Example 3-Application of CM-L / CG Film in Detecting Actual Water Samples

[0104] The CM-L / CG film prepared in Example 1 was cut into 6 mm × 6 mm square films and fixed on a glass slide. The water on the film was absorbed with filter paper, and then 10 μL of secondary water was dripped into it to ensure that the water content of the film was consistent. The initial fluorescence intensity of the film was measured first, and then the glass slide containing the film was immersed in 20 mL of groundwater from three sites (SK1, SK2 and SK3) that had been filtered through filter paper (microporous filter membrane, mixed membrane, pore size of 0.22 μM). 2+ The concentrations were 5, 10 and 20 ppb respectively, and the change in fluorescence intensity was detected. The specific detection results are shown in Table 1.

[0105] Table 1

[0106]

[0107] As shown in Table 1, the same conditions were repeated three times and a good recovery rate (90.60%-104.70%) was obtained. Application Example 4 - Adsorption of lead ions by CM-L / CG film

[0108] First, prepare the concentration to 500 mg / L -1 Pb 2+ Stock solution, from stock solution (500mg L -1 ) in the dilution and fixation adsorption experiment of Pb 2+ concentration.

[0109] The CM-L / CG film prepared in Example 2 was cut into 0.1 g pieces and immersed in 50 mL of Pb 2+ Aqueous solution (50 mg L -1 ) and shake continuously at room temperature to obtain Figure 6 The adsorption kinetic curve is shown. Application Example 5-Adsorption of lead ions by CM-L / CG film

[0110] First, prepare the concentration to 500 mg / L -1 Pb 2+ Stock solution, from stock solution (500mg L -1 ) in the dilution and fixation adsorption experiment of Pb 2+ concentration.

[0111] The CM-L / CG film prepared in Example 2 was cut into 0.1 g pieces and immersed in 50 mL of different initial concentrations (0-400 mg L -1 ) 2+ The mixture was shaken for 180 minutes until the adsorption reached equilibrium and the following Figure 7 The isotherm adsorption curve is shown.

[0112] The sensitive membrane of the present invention has a large number of interconnected pore structures, which not only provides a convenient rapid mass transfer channel inside and outside the membrane, but also increases the membrane and Pb 2+ The contact area between the 2+ key factors.

[0113] The CM-L / CG film can be easily integrated as a solid fluorescence sensing platform for Pb 2+ The ions have an enrichment effect and good stability. When the CM-L / CG film is immersed in a solution containing lead ions, a decrease in fluorescence intensity can be detected. The fluorescence excitation wavelength of the film is 405nm, the emission wavelength is 515nm, the response time is 2min, the detection range is 5-400ppb, and the actual minimum detection is 5.0ppb.

[0114] At the same time, the CM-L / CG film has a great influence on the Pb 2+ ions showed excellent adsorption performance. Pb 2+ The isothermal adsorption curves and kinetic data on the CM-L / CG membrane showed that the adsorption behavior was well described by Langmuir and pseudo-second-order kinetics. The film was used for the simultaneous sensitive detection and effective removal of Pb 2+ It provides a multifunctional platform and also offers new design strategies for the monitoring and purification of heavy metals in contaminated water.

[0115] The preferred embodiments of the present application are described in detail above, but the present application is not limited thereto. Within the technical concept of the present application, the technical solution of the present application can be subjected to a variety of simple modifications, including combining various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed in the present application and belong to the protection scope of the present application.

Claims

1. A coumarin-based fluorescent compound, the structure of which is shown in Formula I: In formula I, X is selected from O or S, L is absent or selected from C1-C6 alkylene; R1 and R2 are the same or different and are independently selected from C1-C6 alkyl groups; R3, R4, R5, R6, R7, R8 and R9 are each independently selected from hydrogen, halogen or C1-C6 alkyl.

2. The coumarin-based fluorescent compound according to claim 1, characterized in that: X is selected from O, L is absent or selected from C1-C4 alkylene; R1 and R2 are the same or different and are independently selected from C1-C4 alkyl groups; R3, R4, R5, R6, R7, R8 and R9 are each independently selected from hydrogen, fluorine, chlorine, bromine or C1-C4 alkyl; preferably, The coumarin-based fluorescent compound is selected from the following compounds:

3. A fluorescence sensitive film comprising a chitosan-based film and the coumarin-based fluorescent compound according to claim 1 or 2, Preferably, the chitosan-based film is combined with the coumarin-based fluorescent compound via chemical bonds and / or intermolecular forces.

4. The fluorescent sensitive film according to claim 3, characterized in that: The loading amount of the coumarin-based fluorescent compound on the chitosan-based membrane is 1 mg / g-30 mg / g, preferably 2.5 mg / g-10 mg / g; and / or The thickness of the fluorescence sensitive film is 10 μm-50 μm, preferably 15 μm-35 μm.

5. A method for preparing a fluorescence sensitive film, comprising the following steps: S1: subjecting the compounds represented by formula A and formula B to a first reaction in a solvent to obtain a reaction product; S2: performing a second reaction on the reaction product of step S1 and a solution containing a chitosan-based membrane; In formula A, R1 and R2 are the same or different and are independently selected from C1-C6 alkyl; R3, R4, R5 and R6 are independently selected from hydrogen, halogen or C1-C6 alkyl; In formula B, X is selected from O or S, L is absent or selected from C1-C6 alkylene; R7, R8 and R9 are each independently selected from hydrogen, halogen or C1-C6 alkyl.

6. The preparation method according to claim 5, characterized in that: In formula A, R1 and R2 are the same or different and are independently selected from C1-C4 alkyl, and R3, R4, R5 and R6 are independently selected from hydrogen, fluorine, chlorine, bromine or C1-C4 alkyl; and / or In formula B, X is selected from O, L is absent or selected from C1-C4 alkylene; R7, R8 and R9 are each independently selected from hydrogen, fluorine, chlorine, bromine or C1-C4 alkyl; Preferably, the compound represented by formula A is selected from the following compounds: The compound represented by formula B is selected from the following compounds:

7. The preparation method according to claim 5 or 6, characterized in that: In step S1, the solvent is selected from C1-C5 alcohol compounds, preferably selected from methanol or ethanol; and / or The molar ratio of the compound represented by formula A to the compound represented by formula B is (0.8-1.2):1; The temperature of the first reaction is 50°C-100°C, preferably 60°C-90°C; and / or The first reaction time is 5h-30h, preferably 10h-20h; and / or The reaction product is recrystallized and then subjected to a second reaction with a solution containing a chitosan-based membrane. Preferably, the recrystallization is performed using a C1-C5 alcohol compound, preferably methanol or ethanol.

8. The preparation method according to any one of claims 5 to 7, characterized in that: In step S2, the mass ratio of the reaction product to chitosan is 0.001-0.5, preferably 0.005-0.1, more preferably 0.005-0.015; and / or The temperature of the second reaction is 5°C-35°C, preferably 10°C-30°C; and / or The second reaction time is 5h-30h, preferably 10h-20h; and / or The solution comprising the chitosan-based membrane is obtained by: Dissolving chitosan in an acid solution to obtain an acid solution of chitosan; mixing the acid solution of chitosan with a polyol, and performing a prepolymerization reaction to obtain the solution containing the chitosan base film; Preferably, the acid solution is selected from one or more of acetic acid, lactic acid and propionic acid; Preferably, in the acid solution, the mass content of acid is 0.5-5%, preferably 0.5-2%; Preferably, the ratio of the mass of the chitosan to the total volume of the acid solution and the polyol is (1-4) g:100 mL, preferably (2-3) g:100 mL, and the volume ratio of the acid solution to the polyol is (95-99):(1-5); Preferably, the polyol is selected from one or more of C2-C6 polyols, preferably ethylene glycol or glycerol.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The preparation method further comprises step S3: evaporating and cooling the reaction product of step S2 to obtain a crude film, and washing the crude film to obtain the fluorescent sensitive film; Preferably, the evaporation temperature is 40°C-65°C; Preferably, the washing comprises washing the crude membrane with water until it is neutral.

10. Use of the coumarin-based fluorescent compound according to claim 1 or 2, the fluorescent sensitive film according to claim 3 or 4, or the fluorescent sensitive film prepared by the preparation method according to any one of claims 5 to 9 in detecting and / or removing heavy metal ions, especially lead ions, in water.

Citation Information

Patent Citations

  • Chitosan-based composite membrane and preparation method thereof

    CN114272769A